The Moral Status of Slavery in Aristotle’s Politics - Kosmadakis, Nikos (Conatus - Journal of Philosophy, 2018)
In this article I will set out to discuss Aristotle’s views on slavery. It is true that Aristotle is the first philosopher to claim in his Politics that some individuals are born slaves by virtue of their nature, therefore he has been accused as being an advocate of slavery, but also of hierarchical discrimination among humans. Against these views I will argue that Aristotle’s thought moves on to the "archetype", thus formulating his view of the particular institution on which he builds his teleological perception of the world.